Sulfur dioxide inhibits mast cell degranulation by sulphenylation of galectin-9 at cysteine 74 - Song, Jiaru; Zheng, Jie; Li, Zongmin; Fu, Ling; Yang, Jing; Li, Kun; Yu, Xiaoqi; Lv, Boyang; Du, Junbao; Huang, Yaqian; Jin, Hongfang (Frontiers in Immunology, 2024)
Objectives: Mast cell (MC) degranulation is a key process in allergic reactions and inflammatory responses. Aspartate aminotransferase 1 (AAT1)-derived endogenous sulfur dioxide (SO2) is an important regulator of MC function. However, the mechanism underlying its role in MC degranulation remains unclear. This study aimed to investigate the mechanism by which endogenous SO2 controlled MC degranulation. Methods: HMC-1 and Rat basophilic leukemia cell MC line (RBL-2H3) were used in the cell experiments. SO2 content was detected by in situ fluorescent probes. MC degranulation represented by the release rate of MC β-hexosaminidase was determined using a colorimetric assay. Sulfenylation of galectin-9 (Gal-9) in MCs and purified protein was detected using a biotin switch assay. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to determine the exact sulfenylation sites of Gal-9 by SO2. Animal models of passive cutaneous anaphylaxis (PCA) and hypoxia-driven pulmonary vascular remodeling were used to investigate the effect of SO2 on mast cell activation in vivo. Site-directed mutation of Gal-9 was conducted to confirm the exact site of SO2 and support the significance of SO2/Gal-9 signal axis in the regulation of MC degranulation. Results: Degranulation was increased in AAT1-knockdowned MCs, and SO2 supplementation reversed the increase in the MC degranulation. Furthermore, deficiency of endogenous SO2 contributed to IgE-mediated degranulation in vitro. Besides, SO2 inhibited IgE-mediated and hypoxia-driven MC degranulation in vivo. Mechanistically, LC-MS/MS analysis and site-directed mutation results showed that SO2 sulfenylated Gal-9 at cysteine 74. Sulfenylation of the 74th cysteine of Gal-9 protein was required in the SO2-inhibited MC degranulation under both physiological and pathophysiological conditions. Conclusion: These findings elucidated that SO2 inhibited MC degranulation via sulfenylating Gal-9 under both physiological and pathophysiological conditions, which might provide a novel treatment approach for MC activation-related diseases.